2010
DOI: 10.5424/fs/2010191-01168
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and outbreaks of Southern Pine Beetle in Honduras

Abstract: Pine forests, consisting primarily of Pinus oocarpa and P. caribaea, cover some 2.5 million hectares and are one of the principal natural resources and a significant foundation for development in Honduras. Historically, these forests have been subjected to ecological impacts and economic losses caused principally by wildfires and, to a lesser but no less significant extent, by the southern pine beetle, Dendroctonus frontalis. According to studies conducted in the United States and beliefs of rural Honduran lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…The restoration of non-breeding spaces at low elevations becomes especially important considering the effects of the degradation of pine forests by the southern bark beetle (Dendroctonus frontalis Zimmermann, 1868), increase of human settlements, and urbanization in the core zone, buffer zones, and areas immediately surrounding La Tigra National Park (Rivera et al 2010;Coello-Balthasar et al 2011;Gomez et al 2020) that threaten the survival of the species during the altitudinal migration. Factors such as these aggravate the historical threats of La Tigra such as the existence of private lands within the park area, illegal logging, forest fires, and the expansion of the agricultural frontier (Richards 1996;Bonta 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of non-breeding spaces at low elevations becomes especially important considering the effects of the degradation of pine forests by the southern bark beetle (Dendroctonus frontalis Zimmermann, 1868), increase of human settlements, and urbanization in the core zone, buffer zones, and areas immediately surrounding La Tigra National Park (Rivera et al 2010;Coello-Balthasar et al 2011;Gomez et al 2020) that threaten the survival of the species during the altitudinal migration. Factors such as these aggravate the historical threats of La Tigra such as the existence of private lands within the park area, illegal logging, forest fires, and the expansion of the agricultural frontier (Richards 1996;Bonta 2005).…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio, la Faja Volcánica Transmexicana es la región en la cual se distribuyen todas las especies de descortezadores, excepto D. jeffreyi, por lo tanto, la presión sobre los pinos será mayor en esta región. Zúñiga et al (1999) El hecho que la temperatura represente una variable importante en la distribución de los descortezadores da soporte a los estudios realizados sobre las variaciones que tendrían las poblaciones de descortezadores con aumentos de temperatura en escenarios de cambio climático (Bentz et al, 2010;Evangelista et al, 2011;Méndez-Encina et al, 2020;Morales-Rangel et al, 2018;Rivera-Rojas et al, 2010). Sin embargo, debemos considerar la relevancia de los hospederos en la distribución de estas especies, tal como se describió en este estudio, ya que son parte principal de su ciclo de vida e incluso se han señalado hospederos preferentes para cada especie de descortezador (Armendáriz-Toledano et al, 2018;Salinas-Moreno et al, 2004;Salinas-Moreno et al, 2010).…”
Section: Discussionunclassified
“…Adicionalmente se han utilizado modelos de distribución de especies, los cuales relacionan las localidades de presencia de las especies con variables ambientales (Elith et al, 2006), para estimar la distribución potencial de descortezadores en México y Norteamérica (Maldonado et al, 2015;Mendoza et al, 2011a;Salinas-Moreno et al, 2010;Santana-Zarza et al, 2020;Sosa et al, 2018). Incluso algunas aproximaciones han incluido escenarios de cambio climático para estimar la distribución futura de estas especies (Bentz et al, 2010;Evangelista et al, 2011;Méndez-Encina et al, 2020;Morales-Rangel et al, 2018;Rivera-Rojas et al, 2010). Sin embargo, aunque estas aproximaciones identifican lugares con condiciones climáticas favorables para la presencia de descortezadores, no evalúan cuáles especies podrían ser susceptibles de ser infestadas por una o varias especies de descortezadores.…”
unclassified
“…Similar situations have occurred in Honduras and Guatemala with D . frontalis [ 38 ]. After a report of increased bark beetle incidence in Michoacán in west-central Mexico, Rubin-Aguirre et al .…”
Section: Introductionmentioning
confidence: 99%
“…During 2010-2012 the state of Durango lost 25% of its forest production and between 2012 and 2013, 43,859 hectares of forest in Chihuahua were damaged by bark beetles [37]. Similar situations have occurred in Honduras and Guatemala with D. frontalis [38]. After a report of increased bark beetle incidence in Michoaca ´n in west-central Mexico, Rubin-Aguirre et al [39] studied Scolytinae communities and found greater beetle prevalence at lower elevations, correlated with higher maximum temperatures.…”
Section: Introductionmentioning
confidence: 99%